A new species of freshwater crab of the genus Sodhiana Yeo & Ng, 2012 (Decapoda: Brachyura: Gecarcinucidae) from southern Iran - Sharifian, Sana; Kamrani, Ehsan; Sharifian, Salim (Zootaxa, 2014)
A new species of freshwater crab, Sodhiana iranica n. sp. (Decapoda: Brachyura: Gecarcinucidae), is described from Bastak, Iran. This is fourth species of Sodhiana Yeo & Ng, 2012, described, and is the second one known from Iran. It can be distinguished from congeners by the form of its carapace and the structure of the male first gonopod.